Lessons from multi-decadal oceanographic monitoring at an estuarine ecosystem in Argentina - Arias, Andres Hugo (2012)
Both climate change and anthropogenic impact are creating a dynamic of continuous changes in ecosystems. While the expected consequences of these changes are global, the occurrence of extreme events and specific environmental problems are usually local or regional phenomenon. In particular, the coastal ecosystems are among the first vulnerable areas to show those changes; in spite of this, are the least studied. The Bahia Blanca estuary, Argentina, is located at 38º 40´ S and 62º 09´ W with an area of 2300 km2. Along the northern shore of the estuary it is found the most important deepwater harbor of the country, where most of the agricultural and industrial products are exported. For the first time, based on multi decadal oceanographic monitoring and meteorological data of this ecosystem, a co-relational analysis approach was outlined considering several documented changes at various trophic levels; namely, phytoplankton and zooplankton assemblages,commercial crustaceans and fisheries. As results, several novel emerging hypotheses regarding cause-and effect relationships were formulated. These unprecedented findings represent substantial information for the focus of the future ecosystem management and research, revealing gaps in the present knowledge of the coastal ecosystem which can be extrapolated to other worldwide coastal systems.